Competing in a hypercompetitive environment : a conceptual framework for new entrants' marketing strategies. - Kee, Chin Siang. (2008)
This research study focuses on the three key mobile service providers in the telecommunications industry of Singapore. Our study aims to determine how these new entrants compete against the incumbents in a hypercompetitives industry, while at the same time examining their moves and counter moves against each other using D’Aveni’s four arenas.